Transport and photophysical studies on porphyrin-containing sulfonated poly(etheretherketone) composite membranes. (December 2021) - Sousa, Joana F.M.; Pina, João; Gomes, Carla; Dias, Lucas D.; Pereira, Mariette M.; Murtinho, Dina; Dias, Paula; Azevedo, João; Mendes, Adélio; Seixas de Melo, J. Sérgio; Pais, Alberto A.C.C.; Pineiro, Marta; et al.
Abstract: The development of efficient and reliable membranes for redox flow batteries (RFBs) with high ionic conductivity and selectivity is challenging. Aiming the development of better membranes, we have synthesized porphyrin-containing sulfonated poly(etheretherketone) (SPEEK). In particular, the effect of water soluble 5, 10, 15, 20- tetrakis ( N -methyl-4-pyridinyl)porphyrin iodide (TMePyPI4 ) and its Cu(II) complex, 5, 10, 15, 20- tetrakis ( N- methyl-4-pyridinyl)porphyrinate copper(II) iodide, (CuTMePyPI4 ), at 0.1–0.3 wt%, have been assessed. Photophysical studies have shown that porphyrins are aggregated in the J-type. The obtained composite membranes show high macroscopic homogeneity and lower ability to sorb water when compared with pristine SPEEK membranes but comparable protonic conductivity. The hydronium diffusion and permeability coefficients suggest that at low porphyrin concentrations an enhancement of proton channels occurs, whilst at high concentration that effect decreases due to the formation of porphyrin aggregates. A similar effect occurs in the permeation of vanadium ions through composite membranes with a remarkable lower permeability and diffusion coefficients when compared with those obtained for Nafion 115 membranes. This along with the improved thermal stability of porphyrin-containing SPEEK composite membranes indicate that these advanced materials can be used for improving the performance of RFBs. Graphical Abstract: ga1 Highlights: SPEEK and porphyrin-containing SPEEK membranes were assessed for RFBs. Porphyrin-containing SPEEK membranes show higher thermal behavior than pristine SPEEK and Nafion. Modified SPEE membranes show remarkable low vanadium crossover values. SPEEK-based membranes show better mass transport performance for RBs than Nafion.